A study on the compressive strengths of stiffened and unstiffened concrete-filled austenitic stainless steel tubular short columns. (15th March 2022) - Elsisy, Amany Refat; Shao, Yong-Bo; Zhou, Man; Hassanein, M.F.
Abstract: Concrete-filled steel tubular columns are currently used in offshore structures, through which the external steel tubes become at risk due to aggressive ocean climate. This has recently led to the introduction of the concrete-filled stainless steel tubular (CFSST) columns, which make use of stainless steel as a superior material resistant to metallic corrosion. However, concrete-filled stiffened stainless steel hollow tubular (CFSSST) columns have not received much attention, although recently they have shown great performance under compression. Accordingly, this paper is devoted to addressing the advantages of using CFSSST columns in practice. Currently, a comparison is made between CFSSST columns and CFSST columns that have the same cross-sectional areas for both the stainless steel and concrete components. A nonlinear finite element (FE) analysis is first generated, using ABAQUS software, for CFSST columns. Then, FE results for CFSST columns are compared with the available experimental results for CFSSST columns. The results show that CFSSST columns provide significantly higher strengths compared to unstiffened columns, which correlates with the significant increase in the strength of the confined concrete compared with equivalent CFSST columns. Furthermore, both strengths of the two column types are compared to EC4 predictions, the results of which appear to be suitable for CFSST columns but conservative for CFSSST columns. For the case of CFSST short columns, a modified version of the continuous strength method is suggested, where a more accurate value of the buckling factor of stainless steel plate is used when it is in contact with concrete. Additionally, a formula is proposed for the lateral confining pressure provided by the stiffened austenitic stainless steel tubes to the concrete core, and used in a suggested design model for CFSSST short columns, for the first time in the literature. Highlights: A finite element model for CFSSST short columns under axial loading is presented. Using ABAQUS, 3D finite element CFSSSTs under axial compression are developed. Differences between stiffened and unstiffened CFSST columns are addressed. The proposed design model is shown to predict well the strengths of CFSSST columns.